Plasma‐polymerized elastomer/conducting polymer composite: Structural and optical characterization. Issue 7 (3rd June 2013) - Mathew, Anisha Mary; Predeep, P.
<x xml:space="preserve">Abstract</x> Plasma polymerization is an excellent and inexpensive tool for growing uniform, ultrathin amorphous and pinhole‐free polymer layer on different substrates and also for forming polymer composites. This work reports the synthesis and characterization of Styrene Butadiene Co‐polymer (SBR) based conducting polymer composites by plasma polymerization using a home built DC plasma polymerization setup. Optical, morphological, and cyclic voltammetric studies reveal an effective formation of composite structure containing SBR and Polyaniline (Pani). The chemical structure of the composite film is studied using FTIR spectroscopy. The films prepared are highly cross‐linked, amorphous in nature and have band gap of 2.8 eV. Moreover, it is found that I2 doping of the composites enhances their conductivity to a desirable value. The band gap energy of the composite film decreases from 2.8 eV to 2 eV by iodine doping. SEM and AFM images show the uniformity in film morphology. The refractive index of the film is found to be 1.87 and dielectric constant is 3.4 at a wavelength 620 nm in the visible region. POLYM. COMPOS., 34:1091–1098, 2013. © 2013 Society of Plastics Engineers